A study on the effectiveness of promotional tools in the promotional strategies used by Bursa Malaysia Berhad in securing the success of the Crude Palm Oil Futures Contract (FCPO) / Zul Hilmi Ab Manaf - Ab Manaf, Zul Hilmi (Faculty of Business and Management, 2007)
In general, Promotional Strategies is an essential tool in order to achieve and to succeed in the business activities. A good and effective also efficient Promotional Strategies will give a favorable impact to the company. Over the years, the Promotional Strategies been studied toward product and market considerations. However, there is no study been done towards Futures and derivatives especially that regarding to Crude Palm Oil Futures Contract (FCPO). The study is basically, undertaken to examine and find out about the important and impact of the Promotional Strategies in order to securing the success of Crude Palm Oil Futures Contract (FCPO). The study also tries to find out whether the Promotional Strategies that been used by Bursa Malaysia Berhad in securing the success of Crude Palm Oil Futures Contract (FCPO) is done efficiently and effectively. Furthermore, the study is to determine which of the Promotional Tools (Impersonal and Personal Communication) that has strong significant relationship in securing the success of Crude Palm Oil Futures Contract (FCPO). The study also wants to find out which of the tools used in the Promotional Strategies have the highest level of effectiveness. Lastly, Recommendations and suggestion on the study have been represented and prepared based on the findings of the research. The recommendations are important for Bursa Malaysia Berhad in dealing with its Promotional Strategies in the future.